2022
DOI: 10.1016/j.wdp.2021.100387
|View full text |Cite
|
Sign up to set email alerts
|

Food security, poverty and household resilience to COVID-19 in Burkina Faso: Evidence from urban small traders’ households

Abstract: Analyses of the effects of the COVID-19 pandemic on food security of urban households and their resilience are increasingly receiving scholarly interest. In Burkina Faso, urban households whose primary activity is trade were the most immediately impacted by COVID-19 due to the closure of markets. The objective of this research was to analyze the effect of income loss due to COVID-19 on food security and poverty among urban small traders’ households by considering their resilience capacity. A survey was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 77 publications
3
23
0
Order By: Relevance
“…Cardarelli et al ( 23 ) contended that although the COVID-19 pandemic initially reduced access to food and disrupted food supply, in the long run, rural households' access to food has increased through federal aid. Ouoba and Sawadogo ( 24 ) reported that the COVID-19 pandemic disease had reduced households' incomes in Burkina Faso by increasing their likelihood of entering poverty. They showed that the households could adjust to the shock (COVID-19) during a long-term period.…”
Section: Introductionmentioning
confidence: 99%
“…Cardarelli et al ( 23 ) contended that although the COVID-19 pandemic initially reduced access to food and disrupted food supply, in the long run, rural households' access to food has increased through federal aid. Ouoba and Sawadogo ( 24 ) reported that the COVID-19 pandemic disease had reduced households' incomes in Burkina Faso by increasing their likelihood of entering poverty. They showed that the households could adjust to the shock (COVID-19) during a long-term period.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used calorie expenditure and consumption indicators to measure food security (Diramo et.al., 2018;Kahsay et.al., 2019;Ruhyana et.al., 2020;Mohammed, et.al., 2021;Getaneh et.al., 2022). In contrast, Ouba and Sawadogo (2022) and Ngema, et.al. (2018), measured food security using a household food consumption and diversity score.…”
Section: Theoretical Underpinningmentioning
confidence: 88%
“…Some assumed resilience as an end itself which led to gauging resilience as a food security status indicator (Olawuyi, 2019;Akinnagbe & Owolabi 2021) and as a 'direct function' of human capital and socio-economic characteristics of individuals (Ojo et al, 2019). Exception is made of Onuoba and Sawadogo (2022) in their study conducted in Burkina Faso which considered just three components of resilience. In the real sense of it, resilience is a multidimensional latent variable (Alinovi et al, 2010;Ciani & Romano 2013;Tefera & Kayitakire 2014) which must be interrogated from several fundamental pillars, components, and indicators proposed by FAO (2016), and used by Béné et al, (2018) as well as d 'Errico et al, (2018).…”
Section: Conceptual and Theoretical Reviewmentioning
confidence: 99%
“…First, there are limited studies that interrogated the synergy between these pair of concepts (resilience capacity with all its pillars, and farmers' food insecurity status). Most of the past related studies treated the concepts singly, while some separately modeled resilience score and food consumption, adaptive capacity pillar and food security, as well as resilience and expenditure (for instance, Wright et al, 2012;Lokosang et al, 2014;Alfani et al, 2015;Wolde-Tsadik et al, 2015;Ojo et al, 2019;Sani & Kemaw, 2019;Akinnagbe & Owolabi, 2021;Onuoba & Sawadogo, 2022). In addition, some of these related studies appeared not to take into consideration the inherent heterogeneity and hidden bias in observational study of this nature, which was given consideration by this study.…”
Section: Contributions To Knowledgementioning
confidence: 99%